Reliability and validity of self-reported assessment of exposure and outcome variables for manual lifting tasks: a preliminary investigation - Yeung, Simon S; Genaidy, Ash M; Karwowski, Waldemar; Leung, P.C (Applied ergonomics, 2002)
The reliability and validity of self-reported assessment of exposure and outcome variables were examined for manual lifting activities among ten physiotherapists. In this study, the participants evaluated the effects of five lifting variables on perceived effort, twice separated by a one-week period. One hundred and sixty-two lifting conditions were evaluated by each subject. The exposure and outcome lifting variables were described in linguistic terms. Intra-class correlation coefficient (ICC 1, 1) analysis revealed a mean value of 0.62 for all lifting activities. The self-reported assessment was cross-validated with the NIOSH lifting index by mapping the linguistic variables into numerical ranges. Moderate correlations ( r=0.54 and 0.53, p<0.01) were obtained between perceived physical exertion/perceived risk and lifting index. The findings of this study provide preliminary indications that human-based methodologies may be further explored on experienced workers.